"Make Every Frame Count": The practice of slow photojournalism and the work of David Burnett. Issue 4 (18th May 2016) - Mendelson, Andrew L.; Creech, Brian
Abstract : This paper presents a case study of the possibilities of slow photojournalism. Over the past decade, award-winning photojournalist David Burnett has used a 60-year-old Speed Graphic film camera to document US political events, several Olympic Games, and the aftermath of Hurricane Katrina, among other projects. His photographs reveal a significantly different aesthetic from contemporary photojournalism and he is celebrated for the perspective his analog photographs offer. This analysis is based on two points of examination: first, a textual analysis of articles and videos discussing the work; and second, a semiotic analysis of the imagery. The examination suggests Burnett's photo aesthetic signifies a longing for an imagined analog, journalistic utopia of yore, where individual journalists had the time and freedom to put care and attention into their work.